A copper-based anti-friction composite coating and its preparation method and application
By setting a base layer in the copper-based friction-reducing coating and controlling the components of Mo, Cu and C, the problems of low oxidation and hardness during the preparation process are solved, and excellent lubricating performance and friction-reducing properties are achieved at high temperatures.
Patent Information
- Application Number
- CN202310594537.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The existing copper-based friction-reducing coatings have problems such as oxidation, low hardness and poor load-bearing capacity during the preparation process, and have a high wear rate under high temperature environments.
By setting up a base layer, the bonding force between the composite coating and the substrate substrate is enhanced, and the composition of the friction reduction functional layer is controlled. The composite coating is composed of three elements: Mo, Cu and C. The Cu and Mo alloys have good high-temperature lubrication Performance, Mo refines grains to improve hardness, C improves lubrication effect.
It effectively reduces the friction coefficient of the coating, improves friction reduction, solves the problems of oxidation and low hardness, and improves the overall performance and service life of the coating.
Smart Images

Figure CN116334565B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-based anti-friction coating and surface lubricating coating preparation, and specifically relates to a copper-based anti-friction composite coating and a preparation method and application thereof. Background Art
[0002] The piston rod is a force transmission part that connects the piston and the working part. It moves back and forth in the piston sleeve during operation. Its head is connected to the external load component, and the outer cylindrical surface of the head should also have wear-resistant and friction-reducing properties. During long-term service, the outer cylindrical surface of the piston head or the piston rod is prone to scratches or collisions. If the specified fit clearance is exceeded, the sealing rubber ring in the piston cylinder will be damaged, causing oil leakage, which will affect the performance of the piston cylinder and even threaten safety in use. Preparing a solid wear-resistant and friction-reducing coating on the surface of the piston rod component can reduce friction loss and increase the service life and service stability of the component.
[0003] Copper-based anti-friction coatings have good lubrication effects during the friction process due to their good ductility and easy shearing properties. They are the preferred materials for tribological problems in the aerospace and automotive industries at 400°C to 500°C. The patent with publication number CN109023211A discloses the use of cold spraying to prepare wear-resistant anti-friction iron brass coatings, which have high strength, toughness, excellent wear resistance, anti-friction, corrosion resistance and load-bearing properties and can be used as friction pair materials for components such as hydraulic actuators. Although cold spraying is carried out under "low temperature" conditions, it is still necessary to use compressed air to cool the temperature of the substrate to no more than 180°C during the spraying process, and grinding and polishing are performed after the spraying is completed. The copper-based anti-friction coating has problems such as oxidation during the preparation process, the preparation process is cumbersome, and the anti-friction performance still needs to be further improved, which limits its use. Other preparation methods such as powder metallurgy, electrospark deposition, laser cladding and thermal spraying are carried out in a relatively harsh high-temperature environment. The powder will oxidize with the remaining working gas and the surrounding gas. The original powder's organizational structure and physical and chemical properties cannot be well preserved, and there are problems such as oxidation, component burning, grain growth, and component segregation. In addition, general copper-based solid lubricants also have low strength and high wear rate at high temperatures.
[0004] Therefore, higher requirements are placed on the friction reduction performance and preparation method of copper-based anti-friction coatings. It is urgent to improve the overall performance of copper-based anti-friction coating materials to better meet the requirements of harsh service conditions. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a copper-based anti-friction composite coating in view of the deficiencies of the above-mentioned prior art. The composite coating is provided with a base layer to enhance the bonding force between the composite coating and the substrate matrix, and the composite coating is formed by controlling the composition of the composite coating, using three elements of Mo, Cu and C, wherein the alloy composed of Cu and Mo has good high-temperature lubrication performance, the Mo element can refine the grains and improve the hardness of the coating, and C has a good lubrication effect and is more likely to adhere to the metal material, which can effectively reduce the friction coefficient of the coating, improve the anti-friction property, and solve the problems of oxidation, low hardness and poor bearing capacity in the preparation process of the copper coating.
[0006] To solve the above technical problems, the technical solution adopted by the present invention is: a copper-based anti-friction composite coating, characterized in that the composite coating consists of a primer layer and an anti-friction functional layer, and the atomic percentage content of each element in the anti-friction functional layer is: Mo 15%~35%, Cu 30%~65%, C 0%~55%.
[0007] The present invention provides a primer layer to enhance the bonding force between the composite coating and the substrate matrix, and facilitates the deposition of the friction-reducing functional layer on the substrate matrix. The composition of the composite coating is controlled, and the composite coating is formed by using three elements of Mo, Cu and C. The alloy formed by Cu and Mo has good high-temperature lubrication performance. Mo and C are added to the Cu matrix. The Mo element can refine the grains and improve the hardness of the coating. C has a good lubrication effect and is more likely to adhere to the metal material, so the friction coefficient of the coating can be effectively reduced, the friction reduction performance can be improved, and the problems of oxidation, low hardness and poor bearing capacity in the preparation process of the copper coating can be solved. The soft metal copper and graphite are evenly distributed in the composite coating, the coating is microscopically dense, and the interface bonding is good. The addition of Mo improves the hardness of the copper-based coating. Graphite, as a lubricating phase, improves the friction coefficient and wear rate of the coating. In the present invention, the content of each element in the primer layer is consistent with the MoCu ratio in the friction-reducing functional layer, and the content of C is removed and converted to obtain the content of each element.
[0008] The above-mentioned copper-based anti-friction composite coating is characterized in that the atomic percentage content of each element in the anti-friction functional layer is: Mo 15%~20%, Cu 30%~48%, C 32%~55%.
[0009] The above-mentioned copper-based anti-friction composite coating is characterized in that the atomic percentage content of each element in the anti-friction functional layer is: Mo 15%, Cu 30%, C 55%.
[0010] The above-mentioned copper-based anti-friction composite coating is characterized in that the base layer is composed of Mo and Cu, and the ratio of the atomic percentage of Mo and Cu in the base layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer; the thickness of the composite coating is 1.0μm~4.0μm, and the thickness of the base layer is 0.2μm~1.0μm. The present invention is easy to prepare by controlling the atomic percentage of Mo and Cu in the base layer. When preparing the copper-based anti-friction composite coating, the Cu target and the Mo target are first opened to deposit the base layer, and then the C target is opened after a certain period of time. Therefore, the ratio of the atomic percentage of Mo and Cu in the base layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer; the present invention controls the thickness of the composite coating to be 1.0μm~4.0μm. Since the film layer will have certain wear during the friction process, it is a consumable layer. When the film layer is too thin, it cannot meet the service life of the coating. If the film layer is too thick, it will cause film stress concentration and cause the film layer to peel off. And the increase in carbon content makes the coating more brittle to a certain extent, so it needs to be controlled at an appropriate thickness; by controlling the thickness of the base layer, the base layer has a better bonding force with the substrate, the base layer has good toughness, and the internal stress of the coating is small.
[0011] The above-mentioned copper-based anti-friction composite coating is characterized in that the substrate base of the composite coating is 35# steel, 40# steel, 45# steel, titanium alloy or cemented carbide; the composite coating adopts physical vapor deposition to first deposit a base layer on the substrate base, and then deposits the anti-friction functional layer, and the physical vapor deposition method is DC magnetron sputtering, radio frequency magnetron sputtering and arc ion plating; the composite coating of the present invention is suitable for preparation by a variety of physical vapor deposition methods.
[0012] In addition, the present invention also provides a method for preparing a copper-based anti-friction composite coating, characterized in that the method comprises the following steps:
[0013] Step 1: Perform Ar ion glow cleaning on the substrate in a vacuum environment to obtain an activated substrate;
[0014] Step 2: The activated substrate obtained in step 1 is sequentially composite-deposited with a base layer and a friction-reducing functional layer to obtain a copper-based friction-reducing composite coating; the composite deposition process is: firstly DC sputtering a Cu target and a Mo target at a power of 60W to 150W to deposit the base layer for a deposition time of 10min to 30min, then DC sputtering a Cu target and a Mo target at a power of 60W to 150W, and radio frequency sputtering a C target at a power of 60W to 120W to deposit the friction-reducing functional layer for a deposition time of 90min to 240min.
[0015] The present invention performs Ar ion glow cleaning on the substrate under vacuum environment, which is used to activate the substrate and improve the film-base bonding force, and then deposits the bottom layer by direct current sputtering Cu target and Mo target, and then keeps the direct current sputtering Cu target and Mo target, and radio frequency sputters C target, and co-deposits the friction reduction functional layer, and the direct current sputtering Cu target and Mo target at a power of 60W~150W is because Mo incorporation will generate Cu-Mo solid solution, thereby strengthening the film so that the hardness is significantly increased, and the set Cu-Mo element ratio can be obtained within the power range, and the ratio has both excellent tribological properties and mechanical properties, if it exceeds the range, the coating hardness will be significantly reduced, and it is not conducive to wear resistance, and the power of C target is within the range of 60W~100W, because the high-carbon Cu-Mo-C coating will exist in the form of amorphous graphite with the increase of carbon target power, which is beneficial to reducing the friction coefficient and improving the friction reduction performance of the coating. However, if the power continues to increase, it will cause the CC bond content to increase and the coating tends to graphitize, and the loose structure of graphite may cause the hardness to decrease, the coating bonding force to decrease, and the deposition thickness is controlled by controlling the deposition time.
[0016] The above method is characterized in that, before the composite deposition in step 2, the target substrate distance is controlled to be 50 mm to 150 mm, the rotation speed of the sample stage is 0 to 30 rpm, the temperature is 100°C to 300°C, and the vacuum degree is 4.0×10 -3 Pa~6.0×10 -3 Pa, and then introduce Ar gas at a flow rate of 10sccm~20sccm, and maintain the vacuum degree at 1.5Pa~2.5Pa, and the substrate bias at 50V~150V.
[0017] The above method is characterized in that the Cu target and Mo target for composite deposition in step 2 can also be MoCu alloy targets.
[0018] The above method is characterized in that the surface hardness of the copper-based anti-friction composite coating in step 2 is greater than 340HV, the bonding force is greater than 35N, and the wear rate is less than 6.7×10 -6 mm 3 / N·mm, and the friction coefficient at room temperature is less than 0.41. The composite coating prepared by the invention is uniform and dense, has moderate hardness, small friction coefficient, and excellent friction reduction performance.
[0019] In addition, the present invention also provides an application of a copper-based anti-friction composite coating, characterized in that the copper-based anti-friction composite coating is applied to a piston rod and a piston cylinder. The composite coating of the present invention is applied to a piston rod to reduce friction and wear between the piston rod and the piston cylinder or an external load component, providing a new technical approach for moving mechanical parts such as pistons.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention provides a primer layer to enhance the bonding force between the composite coating and the substrate matrix, controls the composition of the composite coating, and adopts three elements of Mo, Cu and C to form the composite coating. The alloy composed of Cu and Mo has good high-temperature lubrication performance. The Mo element can refine the grains and improve the hardness of the coating. C has a good lubrication effect and is more likely to adhere to the metal material, which can effectively reduce the friction coefficient of the coating, improve the friction reduction, and solve the problems of oxidation, low hardness and poor bearing capacity in the preparation process of the copper coating.
[0022] 2. In the present invention, soft metal copper and graphite are evenly distributed in the composite coating, the coating is microscopically dense, and the interface bonding is good. The addition of Mo improves the hardness of the copper-based coating. Graphite and soft metal copper are conducive to the formation of a lubricating film. Graphite, as a lubricating phase, improves the friction coefficient and wear rate of the coating, thereby making the coating have excellent friction reduction performance.
[0023] 3. The copper-based anti-friction composite coating deposited by the multi-target magnetron sputtering method of the present invention can avoid the wettability problem between Cu and C when preparing the composite material, and in the preparation of Mo-Cu-C film, the dispersed Mo and C generate Mo2C at high temperature, which can improve the coating structure and interface bonding strength, and the MoCuO4 and MoO3 generated by oxidation can provide good high-temperature lubrication performance. By adjusting the C target current to control the atomic percentage content of C in the composite coating, the anti-friction performance of the composite coating at room temperature can be adjusted. It has good lubrication performance at room temperature to 500°C.
[0024] 4. The copper-based anti-friction composite coating obtained by multi-target magnetron sputtering coating of the present invention has good coating interface bonding and high bonding strength. The coating bonding strength is greater than 35N, the coating hardness is greater than 340HV, and under dry friction conditions, the sliding friction coefficient is less than 0.41 and the wear rate is less than 6.7×10 -6 mm 3 / N·mm, applied to piston components, it can effectively extend the service life of friction parts and improve operating stability.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the surface of the Mo-Cu-C copper-based anti-friction composite coating prepared in Example 1 of the present invention.
[0027] Figure 2 This is a SEM image of the cross section of the Mo-Cu-C copper-based anti-friction composite coating prepared in Example 1 of the present invention.
[0028] Figure 3 This is the element distribution diagram of Mo in the Mo-Cu-C copper-based anti-friction composite coating prepared in Example 1 of the present invention.
[0029] Figure 4 This is the element distribution diagram of Cu in the Mo-Cu-C copper-based anti-friction composite coating prepared in Example 1 of the present invention.
[0030] Figure 5 This is the element distribution diagram of the Mo-Cu-C copper-based anti-friction composite coating C prepared in Example 1 of the present invention.
[0031] Figure 6 This is a morphology diagram of the Mo-Cu-C copper-based anti-friction composite coating prepared in Example 1 of the present invention after a scratch test.
[0032] Figure 7 This is a SEM image of the Mo-Cu copper-based anti-friction composite coating prepared in Example 3 of the present invention.
[0033] Figure 8 This is a diagram of the friction and wear performance of the copper-based anti-friction composite coating prepared in Examples 1 to 3 of the present invention.
[0034] Fig. 9 This is a microhardness test diagram of the copper-based anti-friction composite coating and Cu prepared in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0035] Example 1
[0036] The Mo-Cu-C copper-based anti-friction composite coating of this embodiment is composed of a primer layer and an anti-friction functional layer. The atomic percentage of each element in the anti-friction functional layer is: Mo 15%, Cu 30%, C 55%, and the ratio of the atomic percentage of Mo and Cu in the primer layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer.
[0037] This embodiment includes the following steps:
[0038] Step 1: After polishing the cemented carbide, use acetone and anhydrous ethanol to ultrasonically clean it for 20 minutes, then rinse it with deionized water and blow it dry, and then put it on the sample stage of the vacuum chamber of the magnetron sputtering equipment. Control the target-substrate distance to 150mm, the rotation speed of the sample stage to 30rpm, and turn on the heater to make the temperature in the vacuum chamber 300℃ and the vacuum degree 4.0×10 -3 Pa~6.0×10 -3 Pa, then Ar gas was introduced at a flow rate of 20 sccm, and Ar ion glow cleaning was performed for 10 min at a negative bias voltage of 600 V to obtain an activated substrate;
[0039] Step 2: The activated substrate obtained in step 1 is subjected to composite deposition of a base layer and a friction reduction functional layer in sequence to obtain a Mo-Cu-C copper-based friction reduction composite coating; the composite deposition process is: firstly, a Cu target is DC sputtered at a power of 150 W and a Mo target is DC sputtered at a power of 100 W to deposit the base layer for 30 minutes, and then a Cu target is DC sputtered at a power of 150 W and a Mo target is DC sputtered at a power of 100 W, and a C target is radio frequency sputtered at a power of 120 W to deposit the friction reduction functional layer for 240 minutes; in the composite deposition, the gas pressure is 2.5 Pa and the substrate bias is 150 V.
[0040] Figure 1 This is a SEM image of the surface of the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment. Figure 2 This is the SEM image of the cross section of the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment. Figure 1 and Figure 2 It can be seen that the surface of the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment is smooth and flat, its structure is dense, and it presents a columnar crystal morphology. The thickness of the Mo-Cu-C copper-based anti-friction composite coating is about 3.75 μm.
[0041] Figure 3 This is the element distribution diagram of Mo in the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment. Figure 4 This is the element distribution diagram of Cu in the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment. Figure 5 This is the element distribution diagram of the Mo-Cu-C copper-based anti-friction composite coating C prepared in this embodiment, from Figure 1~Figure 3 It can be seen that the elements in the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment are evenly distributed.
[0042] Figure 6 The morphology of the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment after scratch testing is shown in FIG. Figure 6 It can be seen from the figure that scratches are generated on the surface of the Mo-Cu-C copper-based anti-friction composite coating prepared in this embodiment after the scratch test.
[0043] After testing, the thickness of the composite coating prepared in this embodiment is 3.75 μm, the thickness of the primer layer is 0.5 μm, the surface hardness of the Mo-Cu-C copper-based anti-friction composite coating is 365 HV, the bonding force is 38 N, and the wear rate is 4.7×10 -6 mm 3 / N·mm, and the friction coefficient at room temperature is 0.23.
[0044] The composite coating of this embodiment is applied to the piston rod and the piston cylinder, which has an excellent lubricating effect, effectively prolongs the service life of the piston rod and the piston cylinder, and improves the operating stability.
[0045] Example 2
[0046] The Mo-Cu-C copper-based anti-friction composite coating of this embodiment is composed of a primer layer and an anti-friction functional layer. The atomic percentage of each element in the anti-friction functional layer is: Mo 20%, Cu 48%, C 32%, and the ratio of the atomic percentage of Mo and Cu in the primer layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer.
[0047] This embodiment includes the following steps:
[0048] Step 1: After polishing, the titanium alloy was ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes respectively, then rinsed with deionized water and dried, and then placed on the sample stage in the vacuum chamber of the magnetron sputtering equipment. The target-substrate distance was controlled to be 100 mm, the rotation speed of the sample stage was 20 rpm, and the heater was turned on to make the temperature in the vacuum chamber 200 °C and the vacuum degree 4.0 × 10 - 3 Pa~6.0×10 -3 Pa, then Ar gas was introduced at a flow rate of 15 sccm, and Ar ion glow cleaning was performed for 10 min at a negative bias voltage of 600 V to obtain an activated substrate;
[0049] Step 2, the activated substrate obtained in step 1 is sequentially composite-deposited with a base layer and a friction-reducing functional layer to obtain a Mo-Cu-C copper-based friction-reducing composite coating; the composite deposition process is: firstly, a Cu target is DC sputtered at a power of 140W and a Mo target is DC sputtered at a power of 80W to deposit the base layer, and the deposition time is 10min; then, a Cu target is DC sputtered at a power of 140W and a Mo target is DC sputtered at a power of 80W, and a C target is radio frequency sputtered at a power of 60W to deposit the friction-reducing functional layer, and the deposition time is 180min; in the composite deposition, the gas pressure is 2.0Pa and the substrate bias is 100V.
[0050] After testing, the thickness of the composite coating prepared in this embodiment is 2.5 μm, the thickness of the primer layer is 0.2 μm, the surface hardness of the Mo-Cu-C copper-based anti-friction composite coating is 348 HV, the bonding force is 41 N, and the wear rate is 5.5×10 -6 mm 3 / N·mm, and the friction coefficient at room temperature is 0.3.
[0051] The composite coating of this embodiment is applied to the piston rod and the piston cylinder, which has an excellent lubricating effect, effectively prolongs the service life of the piston rod and the piston cylinder, and improves the operating stability.
[0052] Example 3
[0053] The Mo-Cu copper-based anti-friction composite coating of this embodiment is composed of a primer layer and a Mo-Cu anti-friction functional layer. The atomic percentage of each element in the anti-friction functional layer is: Mo 35%, Cu 65%, and the ratio of the atomic percentage of Mo and Cu in the primer layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer.
[0054] This embodiment includes the following steps:
[0055] Step 1: After polishing, the 35# steel was ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes respectively, then rinsed with deionized water and dried, and then placed on the sample stage of the vacuum chamber of the magnetron sputtering equipment. The target-substrate distance was controlled to be 50 mm, the rotation speed of the sample stage was 5 rpm, and the heater was turned on to make the temperature in the vacuum chamber 100 °C and the vacuum degree 4.0×10 -3 Pa~6.0×10 -3 Pa, then Ar gas was introduced at a flow rate of 10 sccm, and Ar ion glow cleaning was performed for 10 min at a negative bias voltage of 600 V to obtain an activated substrate;
[0056] Step 2: The activated substrate obtained in step 1 is sequentially composite-deposited with a primer layer and a Mo-Cu friction-reducing functional layer to obtain a Mo-Cu copper-based friction-reducing composite coating; the composite deposition process is: firstly, a Cu target is sputtered with a power of 120W and a Mo target is sputtered with a power of 100W to deposit the primer layer for 10 minutes, and then a Cu target is sputtered with a power of 120W and a Mo target is sputtered with a power of 100W to deposit the Mo-Cu friction-reducing functional layer for 90 minutes; the gas pressure in the composite deposition is 1.5Pa and the substrate bias is 50V.
[0057] After testing, the thickness of the composite coating prepared in this embodiment is 1.0 μm, the thickness of the primer layer is 0.2 μm, the surface hardness of the Mo-Cu copper-based anti-friction composite coating is 341 HV, the bonding force is 35 N, and the wear rate is 6.7×10 -6 mm 3 / N·mm, and the friction coefficient at room temperature is 0.41.
[0058] The composite coating of this embodiment is applied to the piston rod and the piston cylinder, which has an excellent lubricating effect, effectively prolongs the service life of the piston rod and the piston cylinder, and improves the operating stability.
[0059] Figure 7 The SEM image of the Mo-Cu copper-based anti-friction composite coating prepared in this embodiment is shown in FIG. Figure 7It can be seen that the surface of the Mo-Cu copper-based anti-friction composite coating prepared in this embodiment is smooth and flat, and its structure is dense.
[0060] Figure 8 The friction and wear performance diagram of the copper-based anti-friction composite coating prepared in Examples 1 to 3 of the present invention is shown in FIG. Figure 8 It can be seen that the copper-based anti-friction composite coatings prepared in Examples 1 to 3 of the present invention have higher wear resistance.
[0061] Fig. 9 The microhardness test diagram of the copper-based anti-friction composite coating and Cu prepared in Examples 1 to 3 of the present invention is shown in FIG. Fig. 9 It can be seen that the copper-based anti-friction composite coatings prepared in Examples 1 to 3 of the present invention have high wear resistance, which is much higher than that of Cu.
[0062] Example 4
[0063] The Mo-Cu-C copper-based anti-friction composite coating of this embodiment is composed of a primer layer and an anti-friction functional layer. The atomic percentage of each element in the anti-friction functional layer is: Mo 20%, Cu 48%, C 32%, and the ratio of the atomic percentage of Mo and Cu in the primer layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer.
[0064] This embodiment includes the following steps:
[0065] Step 1: After polishing, the 40# steel was ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes respectively, then rinsed with deionized water and dried, and then placed on the sample stage in the vacuum chamber of the arc ion plating equipment. The rotation speed of the sample stage was 20 rpm, and the heater was turned on to make the temperature in the vacuum chamber 200 °C and the vacuum degree 4.0×10 -3 Pa~6.0×10 -3 Pa, then Ar gas was introduced at a flow rate of 15 sccm, and Ar ion glow cleaning was performed for 10 min at a negative bias voltage of 600 V to obtain an activated substrate;
[0066] Step 2, the activated substrate obtained in step 1 is sequentially composite-deposited with a primer layer and a friction-reducing functional layer to obtain a Mo-Cu-C copper-based friction-reducing composite coating; the composite deposition process is: turning on the Cu target, the Mo target and the C target, setting the arc current of each target to 100A, pre-evaporating for 10 minutes, removing the oxide skin on the surface of the target material, then adjusting the Cu target current to 80A, the Mo target current to 60A, turning on the Cu| and Mo target power supplies for deposition for 10min, depositing the Mo-Cu primer layer, then adjusting the C target current to 100A, turning on the C target, and depositing for 180min; the gas pressure in the composite deposition is 2.0Pa, and the substrate bias is 100V.
[0067] After testing, the thickness of the composite coating prepared in this embodiment is 4.0 μm, the thickness of the primer layer is 0.2 μm, the surface hardness of the Mo-Cu-C copper-based anti-friction composite coating is 388 HV, the bonding force is 55 N, and the wear rate is 4.6×10 -6 mm 3 / N·mm, and the friction coefficient at room temperature is 0.3.
[0068] The composite coating of this embodiment is applied to the piston rod and the piston cylinder, which has an excellent lubricating effect, effectively prolongs the service life of the piston rod and the piston cylinder, and improves the operating stability.
[0069] Example 5
[0070] The Mo-Cu-C copper-based anti-friction composite coating of this embodiment is composed of a primer layer and an anti-friction functional layer. The atomic percentage of each element in the anti-friction functional layer is: Mo 30%, Cu 50%, C 20%, and the ratio of the atomic percentage of Mo and Cu in the primer layer is the same as the ratio of the atomic percentage of Mo and Cu in the anti-friction functional layer.
[0071] This embodiment includes the following steps:
[0072] Step 1: After polishing, the titanium alloy was ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes respectively, then rinsed with deionized water and dried, and then placed on the sample stage in the vacuum chamber of the magnetron sputtering equipment. The target-substrate distance was controlled to be 100 mm, the rotation speed of the sample stage was 20 rpm, and the heater was turned on to make the temperature in the vacuum chamber 200 °C and the vacuum degree 4.0 × 10 - 3 Pa~6.0×10 -3 Pa, then Ar gas was introduced at a flow rate of 15 sccm, and Ar ion glow cleaning was performed for 10 min at a negative bias voltage of 600 V to obtain an activated substrate;
[0073] Step 2, the activated substrate obtained in step 1 is sequentially composite-deposited with a base layer and a friction-reducing functional layer to obtain a Mo-Cu-C copper-based friction-reducing composite coating; the composite deposition process is: firstly, a Cu target is DC sputtered at a power of 90W and a Mo target is DC sputtered at a power of 60W to deposit the base layer, and the deposition time is 20min; then, a Cu target is DC sputtered at a power of 90W and a Mo target is DC sputtered at a power of 60W, and a C target is radio frequency sputtered at a power of 80W to deposit the friction-reducing functional layer, and the deposition time is 120min; in the composite deposition, the gas pressure is 2.0Pa and the substrate bias is 100V.
[0074] The composite coating of this embodiment is applied to the piston rod and the piston cylinder, which has an excellent lubricating effect, effectively prolongs the service life of the piston rod and the piston cylinder, and improves the operating stability.
[0075] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A copper-based anti-friction composite coating, characterized in that: The composite coating consists of a primer layer and a friction-reducing functional layer. The atomic percentage content of each element in the friction-reducing functional layer is: Mo 15%-20%, Cu 30%-48%, and C 32%-55%.
2. A copper-based anti-friction composite coating according to claim 1, characterized in that: The atomic percentage of each element in the anti-friction functional layer is: Mo 15%, Cu 30%, C 55%.
3. The copper-based anti-friction composite coating according to claim 1, characterized in that: The primer layer is composed of Mo and Cu, and the atomic percentage ratio of Mo and Cu in the primer layer is the same as the atomic percentage ratio of Mo and Cu in the friction reduction functional layer; the thickness of the composite coating is 1.0 μm to 4.0 μm, and the thickness of the primer layer is 0.2 μm to 1.0 μm.
4. The copper-based anti-friction composite coating according to claim 1, characterized in that: The substrate base of the composite coating is 35# steel, 40# steel, 45# steel, titanium alloy or cemented carbide. The composite coating is first deposited on the substrate base by physical vapor deposition, and then the friction reduction functional layer is deposited. The physical vapor deposition method is DC magnetron sputtering, radio frequency magnetron sputtering and arc ion plating.
5. A method for preparing the copper-based anti-friction composite coating according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: Step 1: Perform Ar ion glow cleaning on the substrate in a vacuum environment to obtain an activated substrate; Step 2: The activated substrate obtained in step 1 is sequentially composite-deposited with a base layer and a friction-reducing functional layer to obtain a copper-based friction-reducing composite coating; the composite deposition process is: firstly DC sputtering a Cu target and a Mo target at a power of 60W to 150W to deposit the base layer for a deposition time of 10min to 30min, then DC sputtering a Cu target and a Mo target at a power of 60W to 150W, and radio frequency sputtering a C target at a power of 60W to 120W to deposit the friction-reducing functional layer for a deposition time of 90min to 240min.
6. The method according to claim 5, characterized in that In step 2, before composite deposition, the target-substrate distance is controlled to be 50 mm to 150 mm, the rotation speed of the sample stage is 0 to 30 rpm, the temperature is 100 ° C to 300 ° C, and the vacuum degree is 4.0 × 10 -3 Pa~6.0×10 -3 Pa, and then introduce Ar gas at a flow rate of 10sccm~20sccm, and maintain the vacuum degree at 1.5Pa~2.5Pa, and the substrate bias at 50V~150V.
7. The method according to claim 5, characterized in that The Cu target and Mo target for composite deposition in step 2 are MoCu alloy targets.
8. The method according to claim 5, characterized in that The surface hardness of the copper-based anti-friction composite coating in step 2 is greater than 340HV, the bonding force is greater than 35N, and the wear rate is less than 6.7×10 -6 mm 3 / N·mm, and the friction coefficient at room temperature is less than 0.
41.
9. An application of the copper-based anti-friction composite coating according to any one of claims 1 to 4, characterized in that: The copper-based anti-friction composite coating is applied to a piston rod and a piston cylinder.
Citation Information
Patent Citations
Wear-resisting and friction-reducing iron brass coating for hydraulic actuator cylinder and preparation method thereof
CN109023211A